“I know I shouldn't but …” the inevitable tension of using workarounds to be a “good nurse” - Debono, Deborah; Greenfield, David; Lipworth, Wendy; Carter, David J.; Black, Deborah; Hinchcliff, Reece; Carland, Jane Ellen; Braithwaite, Jeffrey (Frontiers in Health Services, 2025)
IntroductionRules, policies, and technologies are increasingly introduced in healthcare to reduce complexity and iatrogenic harm. One example is the implementation of Electronic Medication Management Systems (EMMS) to minimise medication errors. However, in hospitals where nurses primarily administer medications, research shows that nurses often adopt “workarounds” to overcome barriers in medication administration. This study explored how nurses experienced and perceived the use of workarounds in their daily medication administration practices. Understanding these feelings is crucial, as they are linked to both patient safety and staff retention.MethodsThis ethnographic study was conducted in six wards in two Australian hospitals across 91 shifts, 46 interviews, seven focus groups, and member-checking sessions with nurses and EMMS stakeholders (N = 113 participants). Data analysis used a general inductive approach.ResultsNurses described positive, negative, ambivalent, and conflicting feelings about using workarounds. Some denied the use or tolerance of workarounds, despite them being routinely observed. Most reported a tension between the perceived necessity of workarounds, reluctance to deviate from policy, and the desire to be a good nurse. Workarounds were seen both as the trademark of an expert, mindful nurse and as deviations from the rules, unsafe for both patients and nurses.DiscussionThis study demonstrates challenges to patient safety associated with the tension between the necessity of workarounds and the desire to adhere to policy. This can create stress and anxiety among nurses. They experience a tension at the intersection of the necessity of workarounds to deliver care, to be a good nurse, and the desire to adhere to policy. The associated stress and anxiety can lead to burnout, professional disengagement, and attrition. The study proposes solutions to manage challenges associated with workarounds.ConclusionWorkarounds are an inevitable aspect of healthcare delivery in response to standardisation. Negative perceptions of workarounds may inadvertently contribute to the very harm that standardisation seeks to prevent. A more open dialogue about their use is essential. Recognising their inevitability and equipping nurses to manage them constructively is key to reducing stress, preventing burnout, and enhancing patient safety.